Potential Role of Meiosis Proteins in Melanoma Chromosomal Instability - Scott F. Lindsey; Diana M. Byrnes; Mark S. Eller; Ashley M. Rosa; Nitika Dabas; Julia Escandon; James M. Grichnik (Journal of Skin Cancer)
Melanomas demonstrate chromosomal instability (CIN). In fact, CIN can be used to differentiate melanoma from benign nevi. The exact molecular mechanisms that drive CIN in melanoma have yet to be fully elucidated. Cancer/testis antigens are a unique group of germ cell proteins that are found to be primarily expressed in melanoma as compared to benign nevi. The abnormal expression of these germ cell proteins, normally expected only in the testis and ovaries, in somatic cells may lead to interference with normal cellular pathways. Germ cell proteins that may be particularly critical in CIN are meiosis proteins. Here, we review pathways unique to meiosis with a focus on how the aberrant expression of meiosis proteins in normal mitotic cells “meiomitosis” could impact chromosomal instability in melanoma and other cancers.